2023
DOI: 10.1017/wet.2023.65
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide effects on dormant and postdormant hybrid bermudagrass putting green turf

John M. Peppers,
Shawn D. Askew

Abstract: Herbicide resistance coupled with a dearth of selective herbicide options has increased complexity of annual bluegrass control in hybrid bermudagrass putting greens. Cumyluron, endothall, and methiozolin are herbicides that have controlled annual bluegrass by inhibiting sites of action that are novel compared to herbicides currently used for turfgrass management in the US. However, peer-reviewed literature has no information on hybrid bermudagrass putting green tolerance to these herbicides. Sixteen field stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…Bensulide plus oxadiazon was the only treatment that unacceptably injured creeping bentgrass at any location and had 24 DOT 20 (data not shown), which is consistent with previous reports of creeping bentgrass susceptibility to this herbicide combination (Johnson 1982, 1987). These results are also consistent with previous reports of hybrid bermudagrass tolerance to methiozolin when applied during periods of active growth at labeled rates (Peppers and Askew 2023) and with creeping bentgrass tolerance to methiozolin when treated in fall or spring (Askew and McNulty 2014; Brosnan et al 2013; Hoisington et al 2014).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Bensulide plus oxadiazon was the only treatment that unacceptably injured creeping bentgrass at any location and had 24 DOT 20 (data not shown), which is consistent with previous reports of creeping bentgrass susceptibility to this herbicide combination (Johnson 1982, 1987). These results are also consistent with previous reports of hybrid bermudagrass tolerance to methiozolin when applied during periods of active growth at labeled rates (Peppers and Askew 2023) and with creeping bentgrass tolerance to methiozolin when treated in fall or spring (Askew and McNulty 2014; Brosnan et al 2013; Hoisington et al 2014).…”
Section: Resultssupporting
confidence: 92%
“…preemergence for 4 wk when applied preemergence to bare ground (Koo and Hwang 2013). Methiozolin has a considerable margin of safety when used on creeping bentgrass putting greens (Askew and McNulty 2014;Brosnan et al 2013;Hoisington et al 2014), and recent reports suggest that the product can be safely used on actively growing hybrid bermudagrass putting greens (Peppers et al 2023). The relatively short persistence of methiozolin (Hwang et al 2013) suggests that low-dose, frequent application programs may be needed to maintain season-long weed control as has been shown with other herbicides (Brewer and Askew 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the initial C. dactylon ×transvaalensis root regeneration had already occurred before the first treatment in 2022 based on these differences in green turf cover between years. Previous research has shown that C. dactylon × transvaalensis is more sensitive to methiozolin when treated just before post-dormancy green up compared with midtransition (Peppers and Askew 2023). New root production as C. dactylon × transvaalensis breaks dormancy may cause increased methiozolin absorption that would account for both the increased injury observed in previous studies and loss of methiozolin concentration in the current study.…”
Section: Persistence Of Methiozolin Applied To Cynodon Dactylon × Tra...supporting
confidence: 56%